The Influence Of Back Massage On Insomnia Reduction In Elderly At Wisma Asissi Nursing Home In Sukabumi In 2019 - Indrayani, Triana; Liuri, Kunigunda (Universitas STRADA Indonesia, 2020)
Back massage has many benefits for the human body system such as reducing muscle pain in the cardiovascular system, improving blood circulation and stimulating blood flow throughout the body, also stimulating cell regeneration– and its effects on the nervous system is that it can reduce the risk of disruption of sleeping quality in elderly people. This study used Quasi-Experimental with